Predictive Analytics and Banking Systems Integration: Transforming Financial Services through Digital Innovation - Mani Kiran Chowdary Katragadda (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of predictive analytics with banking systems represents a transformative force in modern financial services, enhancing operational efficiency and customer experience across varied institutional contexts. This technical article examines two significant implementations: PenFed Credit Union’s PANGEN Project, which revolutionizes credit card processing through automated account generation and risk assessment, and the International Finance Corporation’s iPortal/iDesk applications, which facilitate sophisticated fund management across global markets. Both systems exemplify how predictive analytics can anticipate customer needs, personalize offerings, and mitigate risks when properly integrated with core banking infrastructure. The comprehensive article explores system architectures, integration challenges, data standardization protocols, and security considerations that underpin successful implementations. By examining these case studies, the article provides valuable insights into best practices for financial institutions seeking to leverage advanced analytics within their existing banking frameworks, ultimately driving more informed decision-making and enhanced customer value across the financial services sector.